Thermodynamic Origin of Differential Excipient-Lysozyme Interactions - Kalayan, Jas; Curtis, Robin A.; Warwicker, Jim; Henchman, Richard H. (Frontiers in Molecular Biosciences, 2021)
Understanding the intricate interplay of interactions between proteins, excipients, ions and water is important to to achieve the effective purification and stable formulation of protein therapeutics. The free energy of lysozyme interacting with two kinds of polyanionic excipients, citrate and tripolyphosphate, together with sodium chloride and TRIS-buffer, are analysed in multiple-walker metadynamics simulations to understand why tripolyphosphate causes lysozyme to precipitate but citrate does not. The resulting multiscale decomposition of energy and entropy components for water, sodium chloride, excipients and lysozyme reveals that lysozyme is more stabilised by the interaction of tripolyphosphate with basic residues. This is accompanied by more sodium ions being released into solution from tripolyphosphate than for citrate, whilst the latter instead has more water molecules released into solution. Even though protein aggregation is not directly probed in this study, these different mechanisms are suspected to drive the cross-linking between proteins with vacant basic residues, ultimately leading to protein precipitation.